SISTEM KONTROL DAN MONITORING LAMPU TAMAN POLMANBABEL MENGGUNAKAN PANEL SURYA BERBASIS IoT - monica; Muhammad Haz Fatahillah Alfaridsi; Zanu Saputra; Surojo Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Light control in garden lighting facilities generally uses electricity and switches, making it difficult for operators to turn on garden lights. This is the basis for controlling solar lighting using solar input in the form of solar panels and Arduino Uno as a data processing center obtained from current sensors, voltage sensors, and LDR sensors which are used as readers of the state around the lamp. Garden lights use Arduino uno as the main controller, NodeMCU which functions as a communication medium between Android and solar panel-based garden lights by utilizing the Wi-Fi network and applying IoT technology. and monitoring is carried out through an Android application made using Kodular software called Simpuman. From the tests carried out, it can be concluded that the lights can turn on when the hardware is connected to a portable hotspot, the maximum brightness of the lamp is 498.2 mWatt.